PENGARUH PERTUMBUHAN EKONOMI TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN BERAU: PENGARUH PERTUMBUHAN EKONOMI TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN BERAU - Aprilia Kartika (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2020)
This study ains to dertemine the effect of economic growth on original local goverment revenue in Berau Regebcy. The purpose of the researche carried out to determine and analyze the effect of economic growth on original local goverment revenue in Berau Regency. Based on the results of this study, it could be seen that economic growth has a negative effect on local own-source revenues, which is indiacated by a correlation of -0.00467. This means thar if economic growth increases bt 1 % the original regional income decreases by 0.00467% thus that the hypithesis stated can be accepted.